2007
DOI: 10.1002/ejlt.200700014
|View full text |Cite
|
Sign up to set email alerts
|

Lipid damage during frozen storage of Gadiform species captured in different seasons

Abstract: Quality loss of two gadiform fish species (blue whiting, Micromesistius poutassou; hake, Merluccius merluccius) during frozen storage (-30 and -10 7C; up to 12 months) was studied. For this, hydrolytic (formation of free fatty acids, FFA) and oxidative (conjugated dienes, peroxide and interaction compound formation) lipid damage were analysed. For both species, individual fishes captured in two different trials (May and November) were considered. Increasing (p ,0.05) lipid hydrolysis and oxidation (peroxide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
5
26
0
Order By: Relevance
“…The decrease in consumer acceptance towards frozen fish has been related to accumulation of FFAs, because these compounds have deleterious effects on ATPase activity, protein solubility, and cause disagreeable flavours, discoloration, viscosity-related deterioration of the texture (due to interactions between proteins), and oxidise more rapidly to higher molecular weight lipids (triglycerides and phospholipids), thus providing greater accessibility (lower steric effect) to oxygen molecules and other pro-oxidant molecules. FFAs are sometimes quantified to establish whether or not a food product is organoleptically acceptable (Aubourg, Lago, Sayar, & González, 2007;Barthet et al, 2008). The present results demonstrate that the hydrolytic activity is sensitive to freezing temperature and storage time.…”
Section: Resultsmentioning
confidence: 78%
“…The decrease in consumer acceptance towards frozen fish has been related to accumulation of FFAs, because these compounds have deleterious effects on ATPase activity, protein solubility, and cause disagreeable flavours, discoloration, viscosity-related deterioration of the texture (due to interactions between proteins), and oxidise more rapidly to higher molecular weight lipids (triglycerides and phospholipids), thus providing greater accessibility (lower steric effect) to oxygen molecules and other pro-oxidant molecules. FFAs are sometimes quantified to establish whether or not a food product is organoleptically acceptable (Aubourg, Lago, Sayar, & González, 2007;Barthet et al, 2008). The present results demonstrate that the hydrolytic activity is sensitive to freezing temperature and storage time.…”
Section: Resultsmentioning
confidence: 78%
“…Lipids and proteins do not react to form complexes unless the fat or fatty acids are oxidized (Bhattacharya, Sajilata, & Singhal, 2008). Aubourg et al (Aubourg, Lago, Sayar, & González, 2007) attributed the process of lipid oxidation in frozen fish to the action of endogenous enzymes in each species. Endogenous fish enzymes may be active during frozen storage, even at − 20°C (Hwang & Regenstein, 1989).…”
Section: Resultsmentioning
confidence: 98%
“…Aubourg et al (2007) attributed the process of lipid oxidation in frozen fish to the action of endogenous enzymes in each species. Endogenous fish enzymes may be active during frozen storage, even at temperatures of À20°C (Hwang & Regenstein, 1989).…”
Section: Thiobarbituric Acidmentioning
confidence: 98%
“…The decrease in consumer acceptance towards frozen fish has been related to accumulation of FFAs, because these compounds have deleterious effects on ATPase activity, protein solubility, and cause disagreeable flavors, discoloration, viscosity-related deterioration of the texture (due to interactions between proteins), and oxidize more rapidly to higher molecular weight lipids (triglycerides and phospholipids), thus providing greater accessibility (lower steric effect) to oxygen molecules and other pro-oxidant molecules. FFAs are sometimes quantified to establish whether a food product is organoleptically acceptable or not (Aubourg, Lago, Sayar, & González, 2007;Barthet et al, 2008;Bernárdez, Pastoriza, Sampedro, Herrera, & Cabo, 2005;Careche & Tejada, 1994;Labuza, 1971). Refsgaard, Brockhoff, and Jensen (2000) showed that lipid hydrolysis plays an important role in the sensory deterioration of salmon during frozen storage.…”
Section: Free Fatty Acidsmentioning
confidence: 99%